The effects of cultivar and climate zone on phytochemical components of walnut (Juglans regia L.). (22nd January 2020) - Wu, Shutian; Ni, Zhanglin; Wang, Ruohui; Zhao, Baojun; Han, Yongxiang; Zheng, Yuewen; Liu, Feng; Gong, Yonghong; Tang, Fubin; Liu, Yihua
Abstract: The diversity of cultivars and variation in phytochemical components pose a great threat to the security of foods that contain walnut. The nutrient values of walnut are stipulated according to phytochemical components, which are driven by internal and external factors associated with fruit growth. The objective of this work was to investigate the effects of cultivar and climate zone on the phytochemical components of walnuts. First, differences and relationships of phytochemical components in eleven walnut cultivars harvested from northeastern China were analyzed. Almost all individual phytochemical components among cultivars showed significant differences ( p  < .05). The results were submitted to correspondence analysis followed by matrix transformation and factor analysis. Fatty acids, amino acids, and minerals (Ca, Na, Fe, Cu, P, and Zn) for the identification and discrimination of eleven walnut cultivars were authenticated. Furthermore, based on essential microelements, essential amino acids, unsaturated fatty acids, and antioxidants, the walnut cultivars realized the precision position in food application. Finally, we confirmed the effects of climate zones on the phytochemical components of walnuts, with variations up to 142%. The climatic factors precipitation and temperature influenced the formation and accumulation of monounsaturated fatty acids, tocopherols, and most minerals. The findings will open promising perspectives for oriented cultivation of walnuts and future application in the food industry. Abstract : The differences and relationships of 49 phytochemical components and their influence factor (cultivar and climate zone) were comprehensively analyzed. Based on correspondence analysis and specific nutritive characters, the walnut cultivars realized the precision position in the food industry. Precipitation and temperature were the important climatic factors for the formation of MUFA, Ve, and most of the minerals.